Corrosion resistance of a self-healing micro-arc oxidation/polymethyltrimethoxysilane composite coating on magnesium alloy AZ31. (April 2017) - Cui, Lan-Yue; Gao, Shang-Dong; Li, Ping-Ping; Zeng, Rong-Chang; Zhang, Fen; Li, Shuo-Qi; Han, En-Hou
Graphical abstract: Highlights: The MAO/PMTMS coating has a compact morphology with some spherical particles. The MAO/PMTMS coating (thickness = 13.65 μm) possesses a good corrosion resistance. The PMTMS film acts as a physical and blocking barrier. The self-healing of PMTMS film plays an important role in its long-term protection. The PMTMS film peels off due to its swelling and the stress of corrosion products. Abstract: A micro-arc oxidation (MAO)/polymethyltrimethoxysilane (PMTMS) hybrid coating was fabricated via MAO processing and subsequent sealing with alkaline treatment and PMTMS. The surface morphologies, chemical compositions and corrosion resistances of the coatings were investigated using FE-SEM, FTIR, XRD and electrochemical and hydrogen evolution measurements. The results indicated that the alkaline treatment was beneficial to the silane treatment and that the MAO coating was efficiently sealed by the PMTMS film. The MAO/PMTMS coating significantly enhanced the corrosion resistance of the AZ31 alloy due to its self-healing function. Additionally, we suggest and discuss a corrosion mechanism for the coating.